PENGEMBANGAN E-MODUL AJAR PADA CAPAIAN PEMBELAJARAN PROFESI DAN KEWIRAUSAHAAN DIBIDANG INDUSTRI KECANTIKAN DAN SPA FASE E SMK NEGERI 1 LAMONGAN - Irma Nur Fitriya; Novia Restu Windayani; Nia Kusstianti; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2025)
This research aims to develop an E-module for Professional and Entrepreneurship learning in the Beauty and SPA Industry in the Basics of Beauty subject which is implemented at SMK Negeri 1 Lamongan. This research model uses the ADDIE method. This type of research uses "Pre-test post-test One Group Design". The data used is quantitative data obtained based on the suitability of Media Experts, Material Experts and knowledge tests (cognitive). The results of data analysis by media experts obtained an average score of 3.75 (decent). The results of data analysis by material experts obtained an average score of 4.00 (decent). The knowledge competency (cognitive) learning results show a significant difference between before and after being given the Professional and Entrepreneurship learning E-module in the Beauty and SPA Industry. This means that the E-module being developed can help improve learning outcomes.